2018
DOI: 10.1656/045.025.0101
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Status of Native Brook Trout on Laurel Hill, Southwestern Pennsylvania

Abstract: A Brief Introduction to R, the multilevel package and the nlme package

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Approximately 39% of North American freshwater fish species are facing imperilment (Jelks et al., 2008), including populations of Pennsylvania's only native stream salmonid, the brook trout ( Salvelinus fontinalis ; Argent et al., 2018; Cooper, 1983). While previous studies have identified many drivers of brook trout extirpation across their native range (Heft, 2006), a recent survey of brook trout populations in Pennsylvania's Laurel Ridge documented a nearly 60% reduction over a 35‐year period, but could not identify a cause for these drastic population declines (Argent et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 39% of North American freshwater fish species are facing imperilment (Jelks et al., 2008), including populations of Pennsylvania's only native stream salmonid, the brook trout ( Salvelinus fontinalis ; Argent et al., 2018; Cooper, 1983). While previous studies have identified many drivers of brook trout extirpation across their native range (Heft, 2006), a recent survey of brook trout populations in Pennsylvania's Laurel Ridge documented a nearly 60% reduction over a 35‐year period, but could not identify a cause for these drastic population declines (Argent et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…7, 8). The harvestmen not moved actively over surfaces such as it was observed in Maryland (Shultz, 2018), but hidden under stones. This species is predominately parthenogenetic.…”
Section: Caddo Agilismentioning
confidence: 96%
“…The length of palp and legs of specimens from Primorskii Krai are given in Table 2. (Gruber, 1974) USA, Pennsylvania (Shear, 1975) Japan, Hokkaido (Suzuki & Tsurusaki, 1983) Length of body (Suzuki, 1958;Shear, 1975;Cokendolpher & Lee, 1993;Giribet & Kury, 2007;Groh & Giribet, 2015;Shultz & Regier, 2009;Shultz, 2018).…”
Section: Family Caddidae Banks 1892mentioning
confidence: 99%
“…Although their study could not pinpoint the cause of this drastic decline, Argent et al. () postulated that climate change and habitat fragmentation may have played a role. The population genetic patterns of Brook Trout in parts of Appalachia have been documented (Hayes et al.…”
mentioning
confidence: 94%
“…Argent et al. () found that Brook Trout numbers in the Laurel Hill have declined by 64% since 1983 (Sharpe et al. ) despite relatively unchanged habitat and water quality.…”
mentioning
confidence: 99%